Initiating Mental Health Services for Youth Involved in the Juvenile Justice System in Indonesia: Lessons from the US Systems of Care - Juwita Agustin Br Tobing, Septy (Restorative : Journal of Indonesian Probation and Parole System, 2024)
The children’s mental health service has become an inseparable part of the juvenile justice system in developed countries. The United States has successfully reformed the children’s mental health system by utilizing the systems of care framework, embracing its principles and values in the juvenile’s mental health treatments. In contrary, Indonesia as a developing country is still struggling with finding the directions and determining the mental health services framework to design mental health programs, policies, treatments, and services. The juvenile justice system in this country even has no concept of the importance of providing the mental health services for the juveniles. Therefore, this paper aims to examine and to explain the possible efforts that can be implemented in Indonesia by learning from the systems of care practice in the US related to the juvenile mental health services. [Pelayanan kesehatan mental anak menjadi bagian yang tak terpisahkan dalam sistem peradilan bagi remaja di negara maju. Amerika Serikat telah berhasil mereformasi sistem kesehatan mental anak dengan memanfaatkan kerangka berpikir sistem perawatan (systems of care), menganut prinsip-prinsip dan nilai-nilai yang terkanding di dalamnya dalam perawatan kesehatan mental remaja. Sebaliknya, Indonesia sebagai negara berkembang masih berjuang untuk menemukan arah serta menentukan kerangka berpikir pelayanan kesehatan mental untuk digunakan dalam menyusun program, kebijakan, perawatan, dan pelayanan kesehatan mental. Sistem peradilan bagi remaja di negara ini bahkan tidak menyebutkan konsep tentang pentingnya menyediakan pelayanan kesehatan mental bagi remaja. Oleh karena itu, makalah ini bertujuan untuk membahas dan menjelaskan upaya yang memungkinkan untuk diterapkan di Indonesia dengan belajar dari praktek sistem perawatan di Amerika Serikat terkait dengan layanan kesehatan mental remaja.]